Community-Led Initiatives in Language Preservation: Strategies for Endangered Language Documentation and Revitalization - Wa Ode Sinta Watimelu (Pemuda Peduli Publikasi Insan Ilmiah, 2024)
Purpose: The study aims to evaluate the effectiveness of community involvement in language preservation, identify key methods used in documentation and revitalization efforts, and assess the outcomes of these initiatives. Methods: It employs a qualitative approach, including interviews and case studies of community-led language preservation projects in Indonesia. Results: The results indicate that community involvement plays a crucial role in preserving endangered languages by raising awareness of their importance, promoting language use in daily life, and developing culturally relevant learning materials. Conclusions: In conclusion, community-led initiatives are vital for the documentation and revitalization of endangered languages, highlighting the importance of local knowledge and cultural practices in preserving linguistic diversity.